53BP1/RIF1 signaling promotes cell survival after multifractionated radiotherapy. Issue 3 (11th December 2019) - Eke, Iris; Zong, Dali; Aryankalayil, Molykutty J; Sandfort, Veit; Bylicky, Michelle A; Rath, Barbara H; Graves, Edward E; Nussenzweig, André; Coleman, C Norman
Abstract: Multifractionated irradiation is the mainstay of radiation treatment in cancer therapy. Yet, little is known about the cellular DNA repair processes that take place between radiation fractions, even though understanding the molecular mechanisms promoting cancer cell recovery and survival could improve patient outcome and identify new avenues for targeted intervention. To address this knowledge gap, we systematically characterized how cells respond differentially to multifractionated and single-dose radiotherapy, using a combination of genetics-based and functional approaches. We found that both cancer cells and normal fibroblasts exhibited enhanced survival after multifractionated irradiation compared with an equivalent single dose of irradiation, and this effect was entirely dependent on 53BP1-mediated NHEJ. Furthermore, we identified RIF1 as the critical effector of 53BP1. Inhibiting 53BP1 recruitment to damaged chromatin completely abolished the survival advantage after multifractionated irradiation and could not be reversed by suppressing excessive end resection. Analysis of the TCGA database revealed lower expression of 53BP1 pathway genes in prostate cancer, suggesting that multifractionated radiotherapy might be a favorable option for radio-oncologic treatment in this tumor type. We propose that elucidation of DNA repair mechanisms elicited by different irradiation dosing regimens could improve radiotherapy selection for the individual patient and maximize the efficacy of radiotherapy.